An integrated analysis of geophysical data for landslide risk assessment. Issue 1 (1st December 2018) - Suto, Koya; Urosevic, Milovan; Burazer, Milenko; Komatina, Snezana
Abstract : In May 2014, a severe storm caused substantial damage in the Balkan area by floods and landslides. As a contribution of geophysicists and geotechnical engineers to the effort of prevention of further damage, a Geoscientists without Borders (GwB) project was organised by Association of Geoscientists and Environmentalists of Serbia to assess the potential of further occurrence of landslide in the region supported by SEG and many other organisations, governments and individuals of many countries. Local and international experts conducted field data acquisition with students from four countries. The project benefited the students to get practical experience in geophysical fieldwork, local governments received information of landslide risk in their area and the residents of the area were made aware of landslide potential of around their home land. Geophysical surveys with seismic and electric methods were carried out in three phases, June and September 2015 and June 2016, in six locations in Serbia and Bosnia and Herzegovina. About 7000m of seismic data are acquired in the sites where landslide potential is considered high. Lesser amount of electric survey was conducted in the same locations. This paper presents some of the result of the geophysical surveys of some of the project areas comparing seismic reflection, MASW and electric resistivity methods, and subsequent assessment of risk of landslide. This information is used by the engineers of local government in their plan of mitigation of disasters.